Erythema Papulatum Centrifugum: A Case Report of an Underrecognized Annular Erythema - Ketprapakorn N; Suchonwanit P (Dove Medical Press, 2024)
Narikun Ketprapakorn, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat Suchonwanit, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 Ext 4, Email poonkiat@hotmail.comAbstract: Erythema papulatum centrifugum (EPC), also known as erythema papulosa semicircularis recidivans, is a rare dermatological condition characterized by single or multiple annular or semi-annular centrifugally growing lesions surrounded by tiny erythematous papules typically observed on the trunk. EPC is prevalent, particularly in Japan and China, although only a few cases have been reported outside Asia. Herein, we present the case of a 47-year-old female from Thailand who experienced a pruritic annular erythematous rash on her right arm for two months. The diagnosis of EPC was established based on clinical manifestations and confirmed by histopathological examination. The lesions resolved after one month of treatment with 0.1% betamethasone valerate cream and avoiding warm weather. This case report contributes to the understanding of EPC, which may be underrecognized in clinical practice due to its self-limiting nature and frequent misdiagnosis. Furthermore, this article provides a comprehensive review of 17 previously reported cases of EPC, focusing on their detailed descriptions.Keywords: annular erythema, annular lesion, eccrine sweat gland, figurate erythema, perieccrine inflammation, sweating